Immunophenotyping in Autoimmune Diseases and Cancer - Szebeni, Gábor J.; Puskás, László G. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The cooperation of highly specialized cell types maintains the homeostasis of multicellular organisms. The disturbance of that harmony contributes to the development of several diseases. Most of the cellular functions are executed by proteins, so it is essential to investigate biological processes at the protein level. Antibodies, complex biomolecules with high specificity, are used to recognize our protein of interest in a process known as "immunophenotyping". One of the routinely used methods to study cellular proteins is flow cytometry, which detects cell surface or intracellular proteins at single-cell resolution. The other most frequent technique is the traditional immunohistochemical investigation of microscopic sections of human tissues. We called authors to publish their latest data studying cancer or autoimmune diseases by immunophenotyping.